Intraoral Endoscopic Approach to Excision of an Infratemporal Fossa Tumour - Chandrakiran C; Sahiti Nori; Sanjay Patil; Surya Prakash D R (Bengal Journal of Otolaryngology and Head Neck Surgery, 2023)
Introduction: The infratemporal fossa is an inverted pyramid shaped structure that lies at the skull base, posterior to the maxillary sinus. It has a complex anatomy due to its relationship to various important vascular and neural channels. Surgical approaches to this region, via the lateral skull base and access mandibulotomies, have high morbidity. By our minimally invasive intra-oral endoscopic technique, an external incision, bony osteotomies and cranial nerve palsies were avoided with an expedited road to recovery and shorter hospital stay.